2001
DOI: 10.1016/s0005-2736(01)00292-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface-associated serum proteins inhibit the uptake of phosphatidylserine and poly(ethylene glycol) liposomes by mouse macrophages

Abstract: Serum proteins, acting as opsonins, are believed to contribute significantly to liposome-macrophage cell association and thus regulate liposome uptake by cells of the mononuclear phagocytic system (MPS). We studied the effect of serum protein on binding and uptake of phosphatidylglycerol-, phosphatidylserine-, cardiolipin-, and N,N-dioleyl-N,N-dimethylammonium chloride- (DODAC) containing as well as poly(ethylene glycol)- (PEG) containing liposomes by mouse bone marrow macrophages in vitro. Consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 59 publications
5
71
0
1
Order By: Relevance
“…In a typical experimental plan, NPs are incubated in a biological fluid that ideally should replicate the features of the in vivo biological milieu. After incubation, the NPs are recovered by centrifugation, ultrafiltration [60,65] or, more recently, by a combination of size exclusion chromatography and ultrafiltration [66], and extensively washed to avoid contamination of nonbound proteins. Finally, the adsorbed proteins are eluted from the NP surface and analyzed by two different methods: gel-based or gel-free proteomics [67].…”
Section: New Modelmentioning
confidence: 99%
“…In a typical experimental plan, NPs are incubated in a biological fluid that ideally should replicate the features of the in vivo biological milieu. After incubation, the NPs are recovered by centrifugation, ultrafiltration [60,65] or, more recently, by a combination of size exclusion chromatography and ultrafiltration [66], and extensively washed to avoid contamination of nonbound proteins. Finally, the adsorbed proteins are eluted from the NP surface and analyzed by two different methods: gel-based or gel-free proteomics [67].…”
Section: New Modelmentioning
confidence: 99%
“…16,25,26) our results in vitro indicated that increasing FALT did not necessarily prevent doX uptake by Ehrlich ascites carcinoma cells. The intracellular level of doX was different in the liposomes, the order of doX uptake by cells after 30 min incubation being PEG-unmodified liposomal doX= SL2000= SL(2000 : 500= 2 : 1)>SL500, thus the level of cell uptake was affected by the kind of PEG modification of liposomes.…”
Section: Effect Of Mixed Peg-modified Liposomal Doxorubicinmentioning
confidence: 69%
“…20,21 As shown in Figure 2, the cellular uptake efficiencies of both GGLG and M-GGLG liposomes largely declined as a result of serum inhibition in HeLa, HCC1954, MDA-MB-468, and COS-7 cells. The cellular uptake of GGLG liposomes was decreased to 22%-28% of that in serum-free medium.…”
Section: Influence Of Serum On the Cellular Uptake Of Liposomesmentioning
confidence: 96%